Factors Influencing Consumers’ Behavioral Intention to Use E-Hailing Services in Malaysia - Kia Hui Gan; Kok Ban Teoh; Choon Sing Cheong; Li Qing Cheong; Hao Ran Chew; Ting Ting Chia; Yoke Choo Chien; A. J. Ali; Daisy Mui Hung Kee (AIBPM Publisher, 2025)
E-hailing is a service that links passengers with drivers of private cars or taxis by enabling consumers to schedule transportation via a website or mobile app such as GrabCar. In cities and locations with limited access to public transit, e-hailing services have grown in popularity. GrabCar is an e-hailing service that charges a set fee for chauffeured transportation in private vehicles. With GrabCar, users can quickly arrange where they want to be picked up and dropped off, view the estimated cost, and even follow their ride's arrival in real time. This study aims to investigate the factors influencing customers’ behavioral intention to use e-hailing apps- GrabCar in Malaysia. An online survey form was prepared to collect data from 100 respondents. The results indicate that factors including perceived usefulness and price of the GrabCar application have significant influences on the consumer’s behavioral intention to use the e-hailing service, while perceived ease of use and safety also play a role in influencing the consumer’s behavioral intention to use the e-hailing service. This study provides valuable insights and guidance to service providers, which enhances customer satisfaction for future development.